SOLIDARITAS SOSIAL PADA MASYARAKAT PLURALIS YANG SERING MENGALAMI BENCANA BANJIR (Studi pada etnis Cina, India, dan Karo di Kelurahan Polonia, Kecamatan Medan Polonia) - Wistin Monica (Perspektif Sosiologi, 2012)
ABSTRACT Focus in this research is solidarity that happen in pluralist society, they are China, India, and Karo society in the environment III, Kelurahan Polonia. Solidarity among pluralist society caused by floods that often happen in the environment.Various forms of help each other in pluralist society everyday activity makes they do that act when they face the floods. This research use the solidarity theory of Emile Durkheim and the method is qualitative approach with empirical research to see the reality of what happened. The results showed that the solidarity happen when pluralist society face the flood. The society not only ask the same ethnic but also ask the others to evacuate and help each other to put their goods in safe place. The solidarity affected by people who blend each other with intense communication, respect for religious differences and the community institutions called Serikat Tolong-Menolong (STM). Solidarity happen by the similarities between pluralist society that is often face flooding in their neighborhood. Keywords : Solidarity, Pluralist Society, Floods